No truck with the Chilean junta! : trade union internationalism, Australia and Britain, 1973-1980 - Jones, Ann (Australian National Univeristy, A.C.T. : ANU Press, 2014)
When lorry drivers in Northampton slapped stickers on their cabs declaring 'No truck with the Chilean Junta!' they were doing more than threatening to boycott. They were asserting their own identity as proud unionists and proud internationalists. But what did trade unionists really know of what was happening in Chile? And how could someone else's oppression become a means to solidify your own identity? The labour movements of Britain and Australia used 'Chile' as an impetus for action and to give meaning to their own political expression, though it was not all smooth sailing. Throughout the 1970s, social movements and unions alternately clashed and melded, and those involved with 'Chile' were also caught within the unhappy marriage of the cross-cultural left. This book draws together the events and stories of these complex times.
Includes bibliographical references and index.
Keywords: International labor activities -- History; Labor movement -- History; Labor unions -- Australia; Labor unions -- Great Britain; Labor unions -- Chile -- Political activity; Australian